Analysis of error rates and capacity outage of wireless links under jamming and multipath signal fading - Jan Mietzner (IET Communications)
Abstract The author addresses the question, under which conditions an active jammer will be successful in corrupting a wireless communication link, when both the desired link and the jamming link are subject to multipath signal fading. To this end, a simple closed‐form analytical expression is derived for the resulting block‐error probability (BLEP) under Nakagami‐m fading with in general unequal fading parameters for the desired and the jamming link. As a by‐product, a novel expression for the corresponding probability of a capacity outage is obtained. An asymptotic analysis and numerical evaluation of the BLEP expression show that in the single‐antenna case the jammer will indeed be successful in corrupting the wireless link, unless there is a rather high signal‐to‐noise ratio (SNR) advantage for the desired link. This even holds true, when signal fading for the jamming link is significantly more severe than for the desired link. Finally, the case of multiple antennas is considered and the benefits of array processing and diversity reception at the desired receiver are explored. It is found that receive array processing can significantly improve the resulting BLEP, provided that the desired link is characterized by favorable fading conditions. On the other hand, diversity reception can significantly improve the BLEP, if the desired link has favorable SNR conditions.